Indonesia Analisis Strategi Pemasaran Dalam Meningkatkan Penjualan Pada Griya Thya Shop Kabupaten Pinrang - Rani Ariyani; Pratiwi Ramlan; Bahtiar Herman (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2025)
The rapid growth of the skincare industry in Indonesia has triggered increasingly intense competition among business actors, including those in Pinrang Regency. This study aims to analyze the marketing strategies implemented by Griya Thya Shop in increasing the sales of skincare products. This research employed a qualitative method with data collected through observation, in-depth interviews, and documentation. The data were analyzed using data reduction, data display, and conclusion drawing techniques, assisted by NVivo software and SWOT analysis. The results show that the use of social media as a promotional tool, good service quality, competitive pricing, and product management aligned with market trends are the main strategies in boosting sales. However, limited stock of popular products and suboptimal utilization of other digital platforms remain obstacles. An appropriate marketing strategy has been proven to enhance both business competitiveness and sales volume.